RESEARCH ON FORCED SHRINKAGE OF CHIP DURING DRAWING WITH A STEEL BROACH - TELYATNIK, INNA; PALADIYCHUK, YURIY; HOROVYI, ARTUR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper considers the current problem of increasing the productivity and accuracy of machining of helical spline joints by using group cutting broaches. Existing approaches are analyzed and the advantages of using broaches with a group cutting scheme compared to traditional single cutting broaches are determined, in particular, regarding the possibility of increasing the feed per tooth and reducing the number of passes. The main attention is paid to the study of key aspects of the design of the cutting part of helical spline broaches of group cutting. Various methods of chip separation between the teeth of the section (fillets, leaves, chamfers) and their feasibility depending on the geometric parameters of the tool, such as the ratio of the broaches profile width to its diameter and the width of the cutting edge of the tooth, are considered in detail. The features of the construction of the cutting section are analyzed, including the shape of the first and second teeth, as well as the need to compensate for the elastic deformation of the metal by reducing the diameter of the second tooth. The dependence of the design parameters of the broach, in particular the width of the cutting edge, on the characteristics of the processed helical slotted hole was determined. Based on the analysis, practical recommendations were formulated for the selection of optimal chip separation methods and the design of the cutting part of helical slotted broaches of group cutting, which will contribute to increasing the efficiency, accuracy and quality of the broaching process. The results of the study can be used in the development of new and improvement of existing designs of broaching tools for processing complex hole configurations in the mechanical engineering industry.